Sistem Diagnosis Penyakit Tanaman Kentang Menggunakan Metode Fuzzy Tsukamoto (Studi Kasus Pada Balai Pengkajian Teknologi Pertanian Kota Malang) - Achmad Dwi Noviyanto; Nurul Hidayat; Sutrisno Sutrisno (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
The Potato in indonesia is one of the important food, Because has several what nutrition have more so than with rice. The with is e istence of these potato crops the potato farmers have a relatively high economic value. Lately consumers who consume potatoes also tend to increase. The with that level then potato farmers will also add a lot, worried about the more diseases of potato crops that can harm the potato farmers. In potato disease control potato farmers should be able to know potato diseases and their solutions appropriately and correctly. The with application that the author made this can be made in the guidelines of the potato farmers in how to detect and know the solution of disease prevention suffered by the potato plant. In the application that the author made it can detect 10 diseases of potato plants with 37 symptoms suffered. In this application apply the concept of artificial intelligence, by using fuzzy tsukamoto method. The application that we created has been validated by e pert potato plants with a level of accuracy obtained from the system of 100%.